The Phenomenon of Communication Strategies and Their Role in Global and Local Digital Communication - Milosavljević, Ilija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
This paper examines the phenomenon of communication strategies, with a particular focus on their application in the digital environment. Through a theoretical review and analysis of relevant literature, the study defines the concept, dimensions, and factors influencing their development and implementation. Special attention is given to the role of digitalization and globalization in shaping strategies, as well as the specificities of the local context. The paper seeks to contribute to a better understanding of communication strategies and their practical application beyond the business context, to which the term is most commonly associated, while identifying key challenges and opportunities in the contemporary media environment. Furthermore, it emphasizes the need for integrating theoretical knowledge and local „climate“ to improve the strategic approach to communication strategies in Serbia and within the broader global context. The analysis provides a foundation for future research and a more comprehensive integration of communication strategy phenomena tailored to the challenges of the digital age and the overall communication processes in modern society.
Keywords: communication strategies; digital environment; globalization; media communication; Serbia; strategic communication